МЕКТЕПКЕ ШЕКЕМГИ ЖАСТАҒЫ БАЛАЛАРДА ОЙЛАЎ ҚӘБИЛЕТИН РАЎАЖЛАНДЫРЫЎДА ОЙЫН ХЫЗМЕТИНИҢ ӘҲМИЙЕТИ - Джолымбетова, М.М. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of thinking operations and review of research works of psychologists on the development of thinking. The author of the article gives examples in the diagnostics of thinking operations of the pre-school children.
Keywords: psychology; preschool; operation; thinking; service; a player; development; conclusion; comparison; analysis; generalization